Pro SQL Server 2012 Practices - Shaw, Chris; Fritchey, Grant; Bossy, Carlos; Lowell, Jeremy; Shaw, Gail; Johansen, Jesper; Prajdi, Mladen; Pastrick, Wendy; Pot'Vin, Kellyn; Strate, Jason; Roggero, Herve; Belt, TJay; et al. (Apress : Imprint: Apress, 2012)
Pro SQL Server 2012 Practices is an anthology of high-end wisdom from a group of accomplished database administrators who are quietly but relentlessly pushing the performance and feature envelope of Microsoft SQL Server 2012. With an emphasis upon performance-but also branching into release management, auditing, and other issues-the book helps you deliver the most value for your company's investment in Microsoft's flagship database system. Goes beyond the manual to cover good techniques and best practices Delivers knowledge usually gained only by hard experience Focuses upon performance, scalability, reliability Helps achieve the predictability needed to be in control at all times.